Synthesis, structural and electrical properties of double perovskite Sr 2NiMoO 6 ceramics - A. Prasatkhetragarn (2018)
The double perovskite Sr 2NiMoO 6 powders and ceramics were prepared by two different (conventional and precursor) solid-state reaction methods. The phase structure was characterized by XRD and TEM techniques. It has been indicated that single-phase perovskite powders were obtained when calcined in air at 1300°C. However, nano-particles of the size 30-60 nm have been found in powders prepared with the precursor method, while those from the conventional route exhibit large irregular shaped particles with aggregation. The dielectric properties (ε r and tanδ) were also examined in the sintered ceramics. The results showed the transition point at 280°C for conventional route, while no clear phase change was observed in ceramics from the precursor route. These observations clearly indicate that the different starting processes affected the phase formation behavior and the electrical properties of Sr 2NiMoO 6 ceramics. © 2011 Springer-Verlag.